EXIGENŢELE ANGAJATORILOR VIZAVI DE COMPETENŢELE PROFESIONALE ALE TINERILOR SPECIALIŞTI - USM ADMIN (Moldova State University, 2008)
In the present higher education changes context (the Bologna Process adhesion), it is important to consider as central elements of the qualifications evolution problem that must be connected to the work as to market dynamic trends. The em- ployment announcements of different companies, institutions, enterprises, organization, etc. show up a set of conditions, knowledge, capacities, professional and management competences that employers require from the young specialists trained in the present education system, th quality an engagements of which depend on the future specialists employments.